“FAIR TRANSPORT AND GENDER” ACADEMIC CONFERENCE - , Dr. Cristina DRAGOMIR (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Wista Romania in collaboration with Constanta Maritime University (CMU) and the European Centre of Social Responsibility (CERS) is holding the Online Academic Conference on the subject of “Fair Transport and Gender” in the maritime industry. The online conference is scheduled to take place on May, 9th, 2020, at 9.00 AM local time Romania. Fair Transport is a social movement aiming at promoting equitable employment, decent work conditions, environmental protection, and last but not the least quality services of transport. The conference will include a debate on the above-mentioned subject as well as the presentation of scientific research papers that will be published on the site: www.techniumscience.com Please register and confirm participation at : Email: cristinadragomir.umc@gmail.com Phone: +40 726 903 396 Online access credentials will be sent by email after the registration. There is no access fee.